The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1126/sciadv.abm7546
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electron transfer pathways of an electron-bifurcating NiFe-hydrogenase

Abstract: Electron bifurcation enables thermodynamically unfavorable biochemical reactions. Four groups of bifurcating flavoenzyme are known and three use FAD to bifurcate. FeFe-HydABC hydrogenase represents the fourth group, but its bifurcation site is unknown. We report cryo-EM structures of the related NiFe-HydABCSL hydrogenase that reversibly oxidizes H 2 and couples endergonic reduction of ferredoxin with exergonic reduction of NAD. FMN surrounded by a unique arrangement of iron sulfur clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…Bifurcating FeFe-hydrogenases contain three subunits designated HydABC, where HydA contains the catalytic H cluster, the site of reversible H 2 activation. Bifurcating NiFe-hydrogenases also contain homologs of HydABC, where the catalytic H cluster of the FeFe-enzyme is replaced by a [4Fe-4S] cluster, and one of the two additional subunits (HydSL) contain the catalytic NiFe-site (Feng et al, 2022). As shown in Figure 1, in the structurally characterized NiFe-enzyme, HydA and HydB each contain five iron-sulfur clusters, designated A1-A5 and B1-B5, respectively, while HydC contains a single cluster (C1).…”
Section: Phylogeny Of the Hydabc Familymentioning
confidence: 99%
See 4 more Smart Citations
“…Bifurcating FeFe-hydrogenases contain three subunits designated HydABC, where HydA contains the catalytic H cluster, the site of reversible H 2 activation. Bifurcating NiFe-hydrogenases also contain homologs of HydABC, where the catalytic H cluster of the FeFe-enzyme is replaced by a [4Fe-4S] cluster, and one of the two additional subunits (HydSL) contain the catalytic NiFe-site (Feng et al, 2022). As shown in Figure 1, in the structurally characterized NiFe-enzyme, HydA and HydB each contain five iron-sulfur clusters, designated A1-A5 and B1-B5, respectively, while HydC contains a single cluster (C1).…”
Section: Phylogeny Of the Hydabc Familymentioning
confidence: 99%
“…As shown in Figure 1, in the structurally characterized NiFe-enzyme, HydA and HydB each contain five iron-sulfur clusters, designated A1-A5 and B1-B5, respectively, while HydC contains a single cluster (C1). HydB also contains the flavin (FMN) that binds NAD(H) and this subunit also binds Fd (Feng et al, 2022). Herein we have carried out a detailed comparative genome analysis and found that the two HydABC subunits of these two hydrogenases are highly conserved in anaerobic microorganisms.…”
Section: Phylogeny Of the Hydabc Familymentioning
confidence: 99%
See 3 more Smart Citations